Uji Resistensi Larvasida Sintetik Dengan Perbandingan Dosis Pada Larva Culex Sp Di Kelurahan Paccerakkang Kecamatan Biringkanaya Kota Makassar - Widya Larasati Ramly; Hamsir Ahmad; Rostina S; Muh. Saleh (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2022)
The use of larvicides is the most common method used by the community to reduce larval habitat. The dosage of temephos based on WHO is 0.02 mg/l. Abate or temephos can cause resistance if not using the appropriate dose. Resistance is the ability of a vector population to survive against a dose of insecticide that normally kills the vector species. Mosquitoes that have been resistant will be immune or do not die even when exposed to insecticides. This type of research is a pure experiment with a post test only design with a control group design using synthetic larvicides (temephos) with the Susceptibility Test method. Resistance test according to WHO guidelines (susceptibility test) aims to determine changes in the level of susceptibility of vectors before, during and after the use of insecticides. The results obtained after 3 trials within 24 hours at a dose of 0.005mg/l the percentage of mortality of Culex sp. larvae was 98.4%, while at a dose of 0.01mg/l the percentage of mortality of Culex sp. larvae reached 100%, and at a dose of 0.015 mg/l mortality percentage of Culex sp. larvae samples also reached 100%. From the results of this study, it can be concluded that the vulnerability status of Culex sp larvae in the Paccerakang Village, Biringkanaya District, Makassar Regency is still in a vulnerable state or resistance has not occurred. Therefore, this research can be a source of information for local communities in developing control strategies using synthetic larvicides (temephos). Keywords: Resistance, Synthetic larvicides (temephos), Culex sp. larvae.